Direct Loan Cash Management and Data Matching (Reconciliation) (1997)
This guide for institutions of higher education and other schools receiving funds under the William D. Ford Direct Loan Program details required and recommended procedures for the reconciliation process. The reconciliation process is explained to include cash management (the accounting for Direct Loan funds drawn down and disbursed to borrowers) and data matching -- a method of ensuring that all borrower information on the school's system matches the data on the system of the Loan Origination Center. Chapter 1 provides an overview of cash management and data matching activities and records. Chapter 2 focuses on managing the loan process from compiling loan origination records through actual disbursements, adjustments, and canceling disbursements and loans. Chapter 3 is on booking the loan (submission of the loan origination record, the promissory note, and the first actual disbursement record). Chapter 4 covers cash management procedures such as accounting for direct loan funds and determining the drawdown account. The data matching process of loan and cash detail records is the subject of chapter 5. The last chapter is on the reconciliation file and problem resolution. It covers creation of the reconciliation file, the data matching process, problem resolution, and common reconciliation problems/resolutions. (DB)